2020
DOI: 10.1159/000508305
|View full text |Cite
|
Sign up to set email alerts
|

Critical Coarctation of the Aorta in Selective Fetal Growth Restriction and the Role of Coronary Stent Implantation

Abstract: <b><i>Introduction:</i></b> Monochorionic twins are at increased risk of congenital heart defects (CHDs). Up to 26% have a birth weight &#x3c;1,500 g, a CHD requiring neonatal surgery, therefore, poses particular challenges. <b><i>Objective:</i></b> The aim of the study was to describe pregnancy characteristics, perinatal management, and outcome of monochorionic twins diagnosed with critical coarctation of the aorta (CoA). <b><i>Methods:</i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Gijtenbeek et al 14 . reported a series of seven cases of CoA in MCDA pregnancies complicated by sFGR without TTTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gijtenbeek et al 14 . reported a series of seven cases of CoA in MCDA pregnancies complicated by sFGR without TTTS.…”
Section: Discussionmentioning
confidence: 99%
“…In smaller twins, the most common subtype of CHD was CoA, with a prevalence of 1.0% (3/296), which is over 30-times higher compared with the general population (0.03%) 1 . Gijtenbeek et al 14 reported a series of seven cases of CoA in MCDA pregnancies complicated by sFGR without TTTS. As in our series, several pregnancies with CoA in the smaller twin were accompanied by PS in the larger cotwin, with AFD at some point during the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies about CoA-stenting in VLWB < 1,500 g ( 11 ) and in ELWB < 1,000 g ( 9 , 12 ) were published in the last 10 years due to a very small number of patients underwent stenting of aortic coarctation in this very special population. The pre-mounted coronary stent was used for CoA-stenting in all studies included patients weighting under 1,500 g. One case report ( 13 ) about use and limitation Magmaris?…”
Section: Discussionmentioning
confidence: 99%
“…(137) More studies are confirming our encouraging results that CoA stenting is effective and safe in selected small children with severe symptomatic CoA. (137)(138)(139)(140) For the future we should focus more on the long-term safety profile of alternative routes of vascular access (as percutaneous or surgical cutdown of the carotid artery) in VLBW infants. The other challenge is the inherent somatic aortic growth requiring subsequent intervention to remove or modify the stent.…”
Section: Interventions In Preterm Born Very Low Birth Weightsmentioning
confidence: 85%